Diversifying relationships: Russian policy toward GCC - Leonid Issaev (14150040) (2022)
The interaction between Russia and Gulf countries represents the story of ups and downs, severe conflicts and sharp warmings that can largely be explained by the permanently changing role and place of each of these players at the global and Middle Eastern political arenas. After Russia's “return” to the Middle East in 2012–2015, Moscow's foreign policy towards the Gulf can be explained in terms of a bargaining strategy. On the one hand, Russia is trying to underline its importance and relevance to the GCC by putting forward diplomatic and political initiatives. The Kremlin uses its direct or indirect presence in the key regional conflicts such as the Syrian, Libyan and Yemeni civil wars as well as the Israeli-Palestinian conflict and Iran’s nuclear issue. On the other hand, Russia is interested in building up stronger economic cooperation with the GCC, drawing bigger volumes of investments from the Gulf to Russia’s broken economy, as well as coordinating efforts with Saudi Arabia in the global oil market. While, in the near future, the qualitative evolution of Russia’s relations with the GCC is hardly possible, there are still options for their deepening within the current level of interaction between Moscow and the Gulf. Other Information Published in: International Politics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1057/s41311-021-00286-4